Management Protocols for Sepsis and Septic Shock after Craniotomy: Clinical Outcomes and Survival Analysis - Boontoterm, Panu; Sakoolnamarka, Siraruj; Urasyanandana, Karanarak; Fuengfoo, Pusit (Asian Journal of Neurosurgery, 2025)
Central nervous system infections are linked to a substantial rise in perioperative mortality, with postoperative neurosurgical infections being both prevalent and severe. Although the Surviving Sepsis Campaign (SSC) guidelines offer a framework for managing sepsis, their effect on clinical outcomes in neurosurgical patients has yet to be fully explored. The aim of this study was to compare mortality rates and clinical outcomes in neurosurgical patients with sepsis and septic shock treated according to the SSC protocol versus standard care.This single-center retrospective analysis on prospectively acquired data included 159 patients with neurosurgical sepsis and septic shock, divided into two groups: 77 patients managed according to the SSC guidelines and 82 patients receiving standard treatment. Data on baseline characteristics, initial management within the first hour, and 30-day clinical outcomes were collected and analyzed.The mortality rate was significantly lower in the SSC protocol group. Additionally, intensive care unit (ICU) length of stay was significantly shorter, and the number of ventilator- and vasopressor-free days was significantly higher in the SSC protocol group (p < 0.001). Hydrocortisone use was associated with reduced vasopressor requirements and shorter hospital stays (p = 0.001 and p < 0.001, respectively). Thiamine use was linked to a shorter hospital stay (p = 0.023), while continuous renal replacement therapy significantly reduced vasopressor use (p = 0.013).Implementing the SSC protocol within the first hour of treatment significantly reduced mortality, shortened ICU length of stay, and increased the number of ventilator- and vasopressor-free days.
Keywords: central nervous system infections; mortality rate; Surviving Sepsis Campaign; sepsis; protocol; perioperative mortality